Combat Experiences, Pre‐Deployment Training, and Outcome of Exposure Therapy for Post‐Traumatic Stress Disorder in Operation Enduring Freedom/Operation Iraqi Freedom Veterans. (18th January 2012) - Price, Matthew; Gros, Daniel F.; Strachan, Martha; Ruggiero, Kenneth J.; Acierno, Ron
<x xml:space="preserve">Abstract</x> The association between exposure to multiple potentially traumatic events (PTEs) and subsequent increased risk of post‐traumatic stress disorder (PTSD) is well established. However, less is known about the relation between exposure to numerous PTEs, as is typical with military service, and treatment outcome. Furthermore, there has been little research examining military specific protective factors, such as pre‐deployment preparedness, on PTSD treatment response. The current study investigated combat exposure and potential moderators of treatment outcome for exposure therapy in Operation Enduring Freedom/Operation Iraqi Freedom (OEF/OIF) veterans with PTSD. One hundred and eleven OEF/OIF veterans diagnosed with PTSD participated in 8 weeks of exposure therapy. Results indicated that increased combat exposure was associated with a reduced rate of change in PTSD symptoms but not depression symptoms. These findings were consistent across two measures of combat exposure. There was preliminary support for the moderating effect of pre‐deployment preparedness on the association between combat exposure and treatment response. Together, these findings suggest that increased combat exposure is associated with poor treatment response in veterans with PTSD; however, this can be reduced by elevated pre‐deployment preparedness. Copyright © 2012 John Wiley & Sons, Ltd. Key Practitioner Message Increased combat exposure is associated with poorer treatment response. Pre‐deployment training is associated with improved treatment response. PTSD interventions should account for the frequency of combat in military personnel.